Buffalopox - S. V. Borisevich; S. S. Marennikova; L. F. Stovba; A. A. Petrov; V. T. Krotkov; A. A. Makhlai (Вопросы вирусологии, 2016)
Buffalopox is a contagious viral disease affecting milch buffaloes (Bubalus Bubalis) and, rarely, cows. The disease has zoonotic implications, as outbreaks are frequently associated with human infections, particularly in the milkers. Buffalopox is associated with high morbidity (80%). The clinical symptoms of the disease are characterized by wartline lesions on the udder, teats, inguinal region, base of the ears, and over the parotid. In the severe form, generalized rash is observed. Although the disease does not lead to high mortality, it has an adverse effect on the productivity and working capacity of the animals resulting in large economic losses. The outbreaks of buffalopox occurred frequently in India, Pakistan, Bangladesh, Nepal, Iran, Egypt, and Indonesia, where buffaloes are reared as milch animals. The buffalopox is closely related with other Orthopoxviruses. In particular, it is close to the vaccinia virus. There is a view that the buffalopox virus might be derived from the vaccinia virus. It is possible that it became pathogenic to humans and animals through adaptive evolution of the genome by obtaining the virulence genes. PCR is performed for the C18L gene for the purpose of specific detection and differentiation of the buffalopox virus from other orthopoxviruses. The C18L gene encodes the ankyrin repeat protein, which determines the virus host range. The open reading frame of this gene is only 150-nucleotide long as against 453 nucleotide in the vaccinia virus, 756 - in the camelpox virus, and 759 - in the cowpox virus. It can be concluded that a systematic study based on the epidemiology of the virus, existence of reservoirs, biological transmission, and the molecular organization of the buffalopox virus from buffalo, cow, and humans may pave the way to a better understanding of the circulating virus and contribute to the control of the disease using the suitable diagnostic and prophylactic measures.